Analysis of Lean Manufacturing Implementation to Improve Production Efficiency and Reduce Supply Chain Costs Us-ing the Value Stream Mapping Approach - Mochamad Bagus Setiyawan; Slamet Riyadi; Fausta Ari Barata (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
In response to increasing competition in the manufacturing sector, PT X—a copper busbar manufacturing company—implemented Lean Manufacturing supported by Value Stream Mapping (VSM) to improve production efficiency and reduce supply chain costs. This study utilizes VSM, Value Stream Analysis Tools (VALSAT), and Root Cause Analysis (5 Whys) to identify sources of waste and formulate improvement strategies. The analysis identified three dominant wastes: waiting time, product defects, and excess inventory. These were mainly caused by the lack of standardized material procedures, inadequate supporting equipment, and poor integration between the incoming inspection process and the Enterprise Resource Planning (ERP) system. To address these issues, the study proposes installing silica rolls, providing air wipers and flatness tools, developing standardized work instructions, and integrating Internet of Things (IoT) technology with the ERP system for real-time monitoring. As a result of implementing these solutions, PT X successfully reduced its defect rate from 6.23% to 1.32%, decreased lead time, and achieved notable savings in supply chain costs. The findings demonstrate that integrating Lean Manufacturing principles with VSM can effectively eliminate non-value-added activities, streamline production processes, and enhance overall competitiveness. This study reinforces the strategic value of Lean tools in continuous improvement initiatives within the manufacturing industry.